2021
DOI: 10.1080/20008198.2020.1859079
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing group treatment for childhood-abuse related PTSD: a randomized controlled trial

Abstract: Background : Patients with PTSD related to childhood-abuse often experience additional problems such as emotional dysregulation and interpersonal difficulties. Psychotherapy focused on stabilization of symptoms, emotion-regulation, and skills training has been suggested as a treatment for this patient population, either as preparation for further treatment or as a stand-alone intervention. Objective : The present study tests the efficacy of treatment using a group-protocol fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Such findings are in line with evidence from nonoffending populations, which has found individual trauma-focused therapies (such as TF-CBT) to be the most effective (Bisson et al, 2007). Similarly, some studies have found minimal or no significant treatment differences between stabilizing group treatment when compared to individual TAU (Baekkelund et al, 2021; Dorrepaal et al, 2012). In one recent RCT, the stabilization phase was not found to improve outcomes, or difficulties in emotion regulation, when compared to exposure therapy alone (Oprel et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Such findings are in line with evidence from nonoffending populations, which has found individual trauma-focused therapies (such as TF-CBT) to be the most effective (Bisson et al, 2007). Similarly, some studies have found minimal or no significant treatment differences between stabilizing group treatment when compared to individual TAU (Baekkelund et al, 2021; Dorrepaal et al, 2012). In one recent RCT, the stabilization phase was not found to improve outcomes, or difficulties in emotion regulation, when compared to exposure therapy alone (Oprel et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“… Bohus et al, 2020 ; Cloitre et al, 2002 ). However, there is limited evidence that phase-based approaches are superior to interventions that primarily focus on trauma processing, with critics arguing that they are an unnecessary use of clinical time, neither improving outcomes nor reducing drop-out ( Baekkalund et al, 2021 ; de Jongh et al, 2016 ; Oprel et al, 2021 ). There is also great variability in what constitutes stabilisation, what interventions are offered and whether this is provided individually or in a group.…”
Section: Misconceptions About Tf-cbtmentioning
confidence: 99%
“…Many clinicians remain concerned that the positive outcomes of EBTs for PTSD observed in clinical studies are not generalizable to ordinary clinical practice (Riggs et al, 2020 ), despite effectiveness research showing promising results (Eftekhari et al, 2013 ; Ehlers et al, 2013 ). This concern is especially related to patients with more complex presentations and CPTSD since the safety and effectiveness of trauma-focused treatments for CPTSD has been questioned (Bækkelund et al, 2021 ; Cloitre et al, 2010 ). It is argued that the problems with emotion regulation can interfere with the patients’ ability to tolerate trauma processing and that the heterogeneity of symptoms is not sufficiently addressed by standard EBTs (Karatzias & Cloitre, 2019 ).…”
mentioning
confidence: 99%